ANALISIS PENGARUH KEPEMIMPINAN TRANSFORMASIONAL, KEPEMIMPINAN TRANSAKSIONAL DAN MOTIVASI TERHADAP KEPUASAN KERJA - Ronnie Resdianto Masman; Ary Satria Pamungkas (Jurnal Manajemen., 2013)
This study examined the influence of transformational leadership, transactional leadership and motivation to job satisfaction. The samples of this research are 60 employees that worked at a private company in West Jakarta. The data were analyses by multiple regression method. Results indicate that the effects of transformational leadership, transactional leadership and motivation to job satisfaction are indirect. The implications for future research are discussed.